2013
DOI: 10.1002/jbm.b.33014
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional configuration of orientated fibers as guidance structures for cell migration and axonal growth

Abstract: Peripheral nerve injuries can be surgically repaired by suturing the transected nerve stumps or, in case of larger lesions, by the transplantation of an autologous nerve graft. To avoid donor site morbidity, the development of artificial implants is desired. Clinically, hollow conduits have been used for this purpose but are inferior to the autograft because they lack internal guidance cues for Schwann cells and regenerating axons. In this article, we describe the design of a three-dimensional (3D) scaffold co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…A design of a 3D scaffold consisting of parallel fibers embedded in a collagen matrix were developed. Using primary cultures of embryonic chicken DRGs, the results showed that PCL microfibers in the 3D matrix guide the direction of SC migration and axonal growth …”
Section: Nanofibers For Neural Tissue Regenerationmentioning
confidence: 88%
“…A design of a 3D scaffold consisting of parallel fibers embedded in a collagen matrix were developed. Using primary cultures of embryonic chicken DRGs, the results showed that PCL microfibers in the 3D matrix guide the direction of SC migration and axonal growth …”
Section: Nanofibers For Neural Tissue Regenerationmentioning
confidence: 88%
“…*P < 0.05, **P < 0.01, ***P < 0.001, ****P < 0.0001. astrocytes) and collagen hydrogels containing orientated nanofibres. Astrocytes have also been reported to adopt a range of morphological appearances in 3D collagen hydrogels, from simple, rounded cells to a stellate, multiprocess-bearing phenotype (Kriebel et al, 2014;Weightman et al, 2014). The stellate appearance probably reflects the normal morphology of such cells, as seen in the parenchyma of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…A number of different natural and synthetic biomaterials -together with well-defined fabrication techniques -have been used to prepare these neural scaffolds as NGCs. Some of the scaffold materials include collagen, fibrin, agarose, agarose derivatized with Laminin-1 or LN-1 peptides, Matrigel, PCL, PGA, PEG and HEMA [16,18,21,30,31]. Typically, these materials are fabricated with different internal structures or surface textures in order to create a microenvironment for guided axonal bundle regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of spatial guidance in 3D biomaterials is exemplified in neural engineering where micro-patterns are used to promote neuronal development and orient neurite extensions [14][15][16][17][18][19][20][21][22][23][24]. For example, biomaterial-based nerve guidance conduits (NGCs) can be designed to treat severed peripheral nerves by promoting directional sprouting of axons and glial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation